Tree population dynamics of three altitudinal vegetation communities on Mount Cameroon (1989-2004) - Forboseh, P.F.; Sunderland, Terry C.H.; Comiskey, J.A.; Balinga, M. (2011)
Changes in permanent sample plots in the lowland, submontane and montane forests on Mount Cameroon (4,095 m above sea level), an active volcano, are described for 15 years from 1989 to 2004. Throughout the study period, the stocking level of trees with a diameter at breast height (DBH) = 10 cm in the three forests were lower than in pan-tropical stands suggesting a significant impact of volcanic and human-related activities on the vegetation communities on the mountain. Annual mortality rates in the submontane and montane forests were consistent with those reported for comparable altitudinal ranges in the Blue Mountains of Jamaica. The annual mortality rate was higher in the lowland forest than other lowland sites included. Divergence between recruitment and mortality rates was large suggesting that the three vegetation communities have not reached their climax. The seven-year difference in half-life of large trees (with a DBH = 50 cm) in the submontane and montane forests suggests an altitudinal effect on turnover of larger trees that in turn contributes to the frequent small stature of high altitude forests. There was little evidence of an altitudinal effect on species turnover and growth rate. This finding supports generalizations about the zero effect of growth on the stature of high altitude trees. Understanding forest dynamics is crucially important in the management of tropical montane environments and in this instance particularly so given the recent creation of the Mount Cameroon National Park.